When E. Faecalis strikes beyond the globe: Orbital cellulitis requiring exenteration (Indian Journal of Case Reports, 2026)
We report the case of an 80-year-old woman affected by Enterococcus faecalis endophthalmitis complicated by orbital cellulitis. Despite maximal medical therapy, including topical fortified antibiotics, intravitreal injections, and intravenous systemic treatment, infection control was not achieved, and the condition progressed into an orbital abscess with worsening proptosis and ophthalmoplegia. Considering the lack of visual potential and the imminent risk of intracranial spread, a subtotal orbital exenteration was performed. Reconstruction was achieved with a vascularized temporalis muscle flap through a transorbital approach. This case highlights the aggressive nature of E. faecalis ocular infections and supports exenteration as a life-saving measure when conventional therapy fails.